Diabetic Foot Wounds: Which Patients are More Prone to Tetanus?. (4th October 2017) - Kuscu, Ferit; Kurtaran, Behice; Ulu, Aslihan; Evran, Mehtap; Inal, Seza; Komur, Suheyla; Cetiner, Salih; Tasova, Yesim; Zeki Aksu, Hasan Salih
Abstract: Background: Patients who have diabetes and chronic wounds are more prone to tetanus than the other populations. The prevalence of diabetes among patients diagnosed with tetanus was 15%, nearly three times the average expected prevalence of diabetes in the United States. In this study, we aimed to evaluate the tetanus immunization status of the patients with diabetic foot wounds (DFW) and to determine the factors, which may predict to immunity against tetanus. Methods: Patients who admitted to outpatient clinics with DFW were included between 1 January and 31 December 2016. Tetanus antibody levels were measured by a commercial Clostridium tetani 5S IgG ELISA kit. Antibody levels below 0.1 IU/ml were defined as "No reliable protection" and levels above 0.1 IU/ml were defined as "Reliable protection". A questionnaire applied to all patients for detailed diabetes and vaccinating history about tetanus. Results: Ninety-one patients were enrolled to the study, 66 (72.5%) of them were male and 25 (%27.5) of them were female. Mean age was 62 ± 11 years. Sixty-five (71.4%) of the patients had no reliable protection while 26 (28.6%) of them had reliable protection. Tetanus IgG titers were decreasing by the age (Figure). Univariate analysis results between the immune and non-immune groups were demonstrated in Table: In the logistic regression analysis, only patients' age was found statistically significant predictive factor for immunity against tetanus (OR: 1, 114 95% CI: 1, 047–1, 185). Conclusion: We found that elderly patients with DFW have very low rate of immunization against tetanus. Therefore, tetanus vaccination should be given particularly to the elderly patients with DFW without any serological control. Disclosures: All authors: No reported disclosures.